2018
DOI: 10.3390/ijms19113430
|View full text |Cite
|
Sign up to set email alerts
|

Mining Late Embryogenesis Abundant (LEA) Family Genes in Cleistogenes songorica, a Xerophyte Perennial Desert Plant

Abstract: Plant growth and development depends on its ability to maintain optimal cellular homeostasis during abiotic and biotic stresses. Cleistogenes songorica, a xerophyte desert plant, is known to have novel drought stress adaptation strategies and contains rich pools of stress tolerance genes. Proteins encoded by Late Embryogenesis Abundant (LEA) family genes promote cellular activities by functioning as disordered molecules, or by limiting collisions between enzymes during stresses. To date, functions of the LEA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…The correlative expression was calculated according to the ∆∆ Ct method. The expression quantity of CsGADPH gene was used as an internal control [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The correlative expression was calculated according to the ∆∆ Ct method. The expression quantity of CsGADPH gene was used as an internal control [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…These proteins were found to accumulate at high concentrations during the last period of seed maturation, concurrent with dehydration 1,23 . More importantly, it has been demonstrated that their expression may be significantly induced under abiotic stress conditions, such as cold, heat, and drought 15,24,25 . It has been proposed that LEA proteins may be involved in various important functions against abiotic stresses, including the stabilization of membrane structures 2,26,27 , the scavenging free radicals 28,29 , and the sequestering ions 29,30 or biotin 31 etc.…”
Section: Introductionmentioning
confidence: 99%
“…All the CsDehydrin proteins contained the YKS segments which are essential for keeping the capacity to adjust their conformation and maintain cellular homeostasis under stress conditions. Among the cis-regulatory elements of the LEA genes, more than three G-Boxes were registered for each dehydrin, LEA_2, and SMP genes and more than two MBS for dehydrin and LEA_2 subfamily gene [89].…”
Section: Findings Of Novel Genes In Native Plants From Arid Land Areasmentioning
confidence: 99%